Mental health and help-seeking behaviors among Mozambican youth: insights from a post-pandemic National Survey Amidst Internal Conflict - Dadras, Omid (SPRINGER HEIDELBERG, 2025)
Purpose
This study aimed to investigate the prevalence and sociodemographic determinants of major depressive disorder (MDD) and generalized anxiety disorder (GAD) among Mozambican youth aged 15-24 years, as well as their help-seeking behaviors.
Methods
Data from 8,154 youth participants in the 2022-23 Mozambique Demographic Health Survey were analyzed. MDD and GAD were assessed using the PHQ-9 and GAD-7 scales, respectively. Univariate and multivariate logistic regression analyses were conducted to examine associations between sociodemographic factors and mental health outcomes and health-seeking behaviors.
Results
The prevalence of MDD and GAD among Mozambican youth was 7.5% for each condition. However, only 9.3% of those with either MDD or GAD sought help for their symptoms, primarily from family and friends. Females had significantly higher odds of experiencing both MDD and GAD but lower help-seeking behavior as compared to males. Unemployment, lower household wealth, and being single were associated with higher odds of both disorders and lower odds of help-seeking behaviors. Higher education increased the odds of GAD and help-seeking behaviors. Significant regional variations were observed, with conflict-affected regions including Cabo Delgado, Nampula, and Zambezia showing the highest prevalence of MDD and GAD.
Conclusion
This study reveals substantial mental health challenges among Mozambican youth, with notable disparities across sociodemographic groups and regions. The low rates of help-seeking behavior underscore the need for targeted interventions to improve mental health awareness and access to services for socio-demographically vulnerable youth.